Progression and variation of competitive 100 and 200m performance at the 2021 European Swimming Championships - Cuenca-Fernández, F.; Ruiz-Navarro, J. J.; González-Ponce, A.; López-Belmonte, O.; Gay, A.; Arellano, R. (Sports Biomechanics, 2021)
Competitive progressions are necessary to ensure that peak performance occurs when medals are decided. This study aimed to: i) study the coefficient of variation (CV) and performance changes (%d) among swimmers who participated in different rounds (i.e., heats, semi-finals and finals); ii) study the CV changes as a function of FINA-points. A total of 1447 performances were analysed in the 100 and 200 m-races during the Budapest 2021 European-Championships. Linear mixed-effects models were applied for total and split-times to obtain intra-athlete CV and %?. The FINA-points were studied with two-way ANOVA and Pearson`s correlation assessed the relations with CV. The CV in 100 m-races was: 0.48 ± 0.21% for males and 0.50 ± 0.20% for females (d = -0.66%); in 200 m-races: 0.63 ± 0.36% and 0.60 ± 0.34% (d = -0.82%). There were differences in FINA-points between strokes and distances (p < 0.02) associated with higher CV for the 200 m-races (r = 0.37; p = 0.003), indicating changes in performance over the rounds. Swimmers` finalists performed easier during the heats by going slower in the first 50 m-lap; however, some of them would have little chance of qualifying during major championships because some events were below FINA-points world-standards.